Influence of process parameters on the interlayer bond strength of concrete elements additive manufactured by Shotcrete 3D Printing (SC3DP). (August 2020) - Kloft, Harald; Krauss, Hans-Werner; Hack, Norman; Herrmann, Eric; Neudecker, Stefan; Varady, Patrick A.; Lowke, Dirk
Abstract: Shotcrete 3D Printing (SC3DP) is a novel robot-guided AM technology developed at Technische Universität Braunschweig in the environment of the Digital Building Fabrication Laboratory (DBFL). For successful automation, it is crucial to understand and redefine the entire concrete spraying process with all its interdependent parameters. This paper presents the basic principles of the SC3DP technology together with the results of a comparative study on the influence of the two concrete printing techniques extrusion and SC3DP on the interlayer bond strength. In particular, the effect of different time intervals between the deposition of two adjacent layers regarding mechanical properties (bond strength) is investigated. As will be shown, the SC3DP method allows convenient mechanical properties although the printed samples exhibit distinct anisotropies. The reasons are discussed based on investigations of the air void distribution by micro CT and mechanical test results.